Formulasi Sediaan Gel dan Uji Aktivitas Bagian Tanaman Nanas Sebagai Sun Protection Factor - Yulinar, Renitha; Rahmawati, Dewi Rahmawati; Yuwanda, Alhara (Health Information : Jurnal Penelitian, 2023)
Excessive sun exposure has a very bad impact on health especially on the face. Therefore, pineapple peel extract is an active ingredient in sunscreen gel formulations. Which contain flavonoid, tannin and saponin compounds which have sunscreen activity. The research method includes identifying pineapple plant samples. Next, a phytochemical screening test to determine the compound content in the extract. Then evaluate the formulation of the pineapple gel preparation which includes organoleptic examination, pH, spread ability and viscosity, test the stability of the pineapple gel preparation for 8 weeks. and measure the SPF value of pineapple peel extract and pineapple gel preparations using a UV-Vis spectrophotometer, as well as irritation testing on pineapple gel preparations using the Draize method. The stability test showed that the pineapple gel preparation remained stable for 8 weeks. SPF measurements show that pineapple peel extract and pineapple gel preparations have quite high SPF values. In conclusion, pineapple peel extract has the potential as an active ingredient in sunscreen gel formulations. The prepared pineapple gel preparation has good characteristics and shows good stability for 8 weeks.